Geogenic Contamination: Hydrogeochemical processes and relationships in Shallow Aquifers of Ibadan, South-West Nigeria - Amanambu, Amobichukwu Chukwudi (Bulletin of Geography. Physical Geography Series, 2015)
The result of the spatial analysis as applied to the hydrogeochemical data set in the shallow aquifer of Ibadan provides an insight into the underlying factors controlling hydrogeochemical processes in the area. A total of thirty drinking water samples (six samples each from the five major lithologic formations of the study area) were collected from shallow aquifers during the rainy and dry season. Atomic Absorption Spectrophotometry (AAS) and the Beckan DU-7500 single beam spectrophotometer were used to determine concentrations of arsenic, iron and fluoride in drinking water samples and the concentrations of other chemical parameters that could affect the concentrations of the geogenic contaminants including Ca, Mg, Na and SO4 2- were also analysed. pH and TDS were also determined. The Pearson Correlation and Factor Analysis were used to examine the relationship between the geogenic contaminants and concentration of other hydrogeochemical parameters while isopleth maps were drawn to ascertain lines of equal geogenic concentration (Isogeogenic lines). Factor analysis reduced the dataset into three major components representing the different sources of the contaminant. Major contributors to factor 1 and 3 (Salinization and Sulphate factors respectively) are natural phenomena while factor 2 is partly geogenic. The Isogeogenic lines show places of equal geogenic concentration and also with 3D Elevation modelling showed a high peak of Arsenic and Fluoride in the Sango area. The correlation test showed that there is a positive relationship between As and SO4 2- 0.889 (P < 0.05) and also a positive relationship between As and Mg 0.43 (P < 0.05). The significant relationship between As and SO4 2-, shows a partly geogenic source resulting from the reduction of sulphate to sulphide for the mobilization of As. The positive relationship between Fluoride and pH 0.242 (P > 0.05) implies that the concentration of F within the rock formation depends on high pH value.